Political Participation of Members of the Indonesian Youth National Committee of Medan City in the 2020 Medan City Regional Head Election - Ardiansyah Putra, M. Ricky; Mhd Ricky Ardiansyah putra; Mhd Ricky Ardiansyah putra (Jurnal Transparansi Publik (JTP), 2024)
Currently, educational institutions are a means for socialization and political education. Young people in the community can join and join existing organizations. This makes it easier for young people to show their political participation. Joining an organization helps young people to become leaders, speakers, and activists. Through a qualitative approach, an in-depth interview was conducted with one of the youth organizations of the Indonesian National Youth Committee (KNPI) in Medan City to find out the political participation carried out by youth people in the election of mayor and deputy mayor through the Medan City KNPI organization. The results of this study show that the political participation shown by the Medan City KNPI Members in the provincial government election in 2020 is by determining one pair of candidates they will support. The form of political participation carried out by the Medan City KNPI to the candidate pairs they have chosen is by forming volunteers among the youth, building communication and socialization to young people groups to support the candidate pairs they have chosen, escorting the votes of the candidate pairs from each polling station and participating in escorting the results of the votes to the Medan KPU office.